DESIGN THINKING E AUTORIA COLETIVA:: A EXPERIÊNCIA DE PRODUÇÃO DE DOCUMENTÁRIOS SOBRE OS DESAFIOS DAS MULHERES NO ESPORTE NO CURSO DE EDUCAÇÃO FÍSICA - Ferreira, Jose Ricardo Lopes; SAntos, Silvan Menezes dos (Revista Docência e Cibercultura, 2025)
This study aimed to report the experience of producing a documentary on the challenges of women in sports, developed by students of the Physical Education course, using the Design Thinking methodology as a central approach. The research, qualitative and descriptive in nature, was based on an experience report, with data collection through participant observation, field diaries, audiovisual records, and semi-structured interviews, analyzed using thematic content analysis. The Design Thinking methodology, divided into stages of problem understanding, solution design, prototyping, and implementation, proved effective in promoting collaborative authorship, creativity, and critical thinking. The results showed that the production of the documentaries broadened students’ understanding of gender inequalities in sports, preparing them to act more consciously and inclusively. The experience also highlighted challenges in teamwork, such as the lack of commitment from some members, but reinforced the importance of collaboration and individual responsibility. It was concluded that the activity was an innovative pedagogical tool, integrating theory and practice in a meaningful way and contributing to the training of more engaged and critical professionals.